Togo : 2009 Article IV Consultation and Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation discusses that a nascent recovery in Togo's economy is expected to be offset in 2009 by the impact of the global recession. The authorities have reiterated their commitment to the Poverty Reduction and Growth Facility (PRGF)-supported program and aim to accelerate growth-enhancing structural reforms. Executive Directors have commended the Togolese authorities for their strong implementation of economic policy and reforms, despite the adverse global and domestic circumstances. They have also welcomed the authorities' intention to continue to focus on targeted measures to mitigate the social impact of shocks.